The History of Development of Pharmacologic and NonPharmacologic Treatment of Pediatric Epilepsy - Habibi, Mitra; Ahmad, Saba; Sinsioco, Claudine (Journal of Pediatric Epilepsy, 2016)
Epilepsy is a common childhood neurological disorder in the United States. Current strategies for treatment of epilepsy in this population include trials with different antiepileptic drugs, vagal nerve stimulator, and ketogenic diet. Development of both pharmacologic and nonpharmacologic treatments in children should take into account their specific pharmacokinetic requirements as well as other ethical and practical challenges that exist for this population. As a result, in many instances detailed information on historical developments of these treatments in children is incomplete or lacking.
Keywords: children; epilepsy; antiepileptic drugs; historical development